University autonomy: Improving educational output - Jo Ritzen (IZA World of Labor, 2016)
University autonomy and funding is an important aspect in university-level education due to its impact on graduates' competencies, and on the quality and quantity of research produced. Political factors influence the amount of autonomy allotted to public universities in specific countries. There is sufficient evidence to suggest that an increase in autonomy for universities would provide better educational outcomes and have a direct impact on labor market productivity. However, the debate on autonomy has been overshadowed by discussions on tuition fees and student aid in political circles.
Keywords: I22; I23; I28; 330; university autonomy; university funding; university education; university research; labor productivity